2009
DOI: 10.1021/la902403f
|View full text |Cite
|
Sign up to set email alerts
|

A Thermochromic Thin Film Based on Host−Guest Interactions in a Layered Double Hydroxide

Abstract: Optically transparent thin films with thermochromic properties have been fabricated by means of cointercalation of different molar ratios of 4-(4-anilinophenylazo)benzenesulfonate (AO5) and sodium dodecylbenzene sulfonate (SDS) into the galleries of a ZnAl layered double hydroxide (LDH). The X-ray diffraction (XRD) patterns of these thin films show that they are assembled in a highly c-oriented manner, and the basal spacing ranges from 2.95 to 2.63 nm with varying AO5/SDS molar ratio. The preferential orientat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…An effective way to enhance the thermochromic performances of this dye is to choose a suitable host matrix for tuning its molecular environment. Wang et al [25] have fabricated transparent thin films based on AO5 and sodium dodecylbenzene sulfonate (SDS) cointercalated in LDH, which show a fast and repeatable thermochromic behavior. By the use of temperature-dependent UV/visible absorption spectrophotometer, it was observed that the 10% AO5-LDH thin film shows the highest thermochromic efficiency.…”
Section: Ldh-based Physicalmentioning
confidence: 99%
See 1 more Smart Citation
“…An effective way to enhance the thermochromic performances of this dye is to choose a suitable host matrix for tuning its molecular environment. Wang et al [25] have fabricated transparent thin films based on AO5 and sodium dodecylbenzene sulfonate (SDS) cointercalated in LDH, which show a fast and repeatable thermochromic behavior. By the use of temperature-dependent UV/visible absorption spectrophotometer, it was observed that the 10% AO5-LDH thin film shows the highest thermochromic efficiency.…”
Section: Ldh-based Physicalmentioning
confidence: 99%
“…This is one of the main bottlenecks in developing optical devices with superior optical properties based on the molecular isomerization. LDH nanosheets can provide the organic Journal of Nanomaterials The correlation between the absorbance of the band at 445 nm and temperature over a heating-cooling cycle [25]. chromophores with a rigid and ordered microenvironment, in which the severe interpenetration of the cis-trans groups may be restrained by the isolating effect of the 2D nanosheets.…”
Section: Photoinduced-responsive Materialsmentioning
confidence: 99%
“…It was well known that this tautomerism is very sensitive to the surrounding environment; therefore, it has been widely used as thermal sensors and in molecular memory storage. In order to further modulate the environment in an inorganic matrix, AO5 was co-intercalated with sodium dodecylbenzene sulfonate (SDS) into the interlayer of LDH [112]. The absorption [99] band at 363 nm at room temperature is attributed to the absorption of A-form, and the intensity increases with elevated temperature (Fig.…”
Section: Detection Of Chemical Substancesmentioning
confidence: 99%
“…However, the research on piezochromic luminescent (PCL) materials remains relative seldom The correlation between the absorbance of the band at 445 nm and temperature over a complete heating-cooling cycle (inset shows the corresponding digital photographs) [112] Scheme 3 Tautomeric equilibrium between the A-Form and H-Form of AO5 [112] compared with other environment-responsive materials (such as temperature-, pHand HMI-sensitive materials). Therefore, the investigation on PCL materials with excellent reversibility, repeatability, and rapid responsiveness is still a challenge [168,169].…”
Section: Pressure Sensormentioning
confidence: 99%
“…Therefore, it can be anticipated that the incorporation of an anionic azo dye into an LDH matrix will give rise to a new kind of photoresponsive material with the following features: first, the LDH host layers provide an ordered microenvironment for the distribution and alignment of the azobenzene groups within the available free space, which may reduce the barrier for isomerization; second, the presence of the inorganic LDH host matrix can improve the thermal and optical stability of the intercalated organic dye. In our previous work, transparent thin films were fabricated that contained AO5 and sodium dodecylbenzene sulfonate (SDS) co-intercalated in LDH, which showed reversible and repeatable thermochromic behavior based on the tautomerism of the AO5 between the azo A-form and the hydrazone H-form [24]. In this work, we further studied the photochromic behavior of an interlayer of AO5 based on its trans-cis isomerization.…”
mentioning
confidence: 99%